The *volja-type Accent in Slavic - Kapović, Mate (2007)
In this paper, Slavic nouns with the suffix *-ja and fixed neo-acute on the root (like *vò ľā « will» or *sũ šā « drought» ) are closely examined. None of the previous explanations, which are here considered, have proven entirely satisfactory. In the paper, it is concluded that the *vò l'ā -type nouns are mostly young derivatives with the *-ja suffix, which thus belong to the default accentual paradigm b. There is no retraction in *-ja nouns in a. p. a (*tǫ ̋ ča « hail, storm etc.» ) or in a. p. c (*dū ša̍ , *dȗ šǫ ). Some problematic words (like *svě ̄ ťa̍ , *svě ̄ ťǫ ̍ « candle» ) are also discussed.
Projekt MZOS
ENG